Investigation of the effect of free fatty acids on cell growth and Cytokine secretion - Moftah, Souad; Eljaki, Abdelhakim; Elmestiri, Fatma; Alrefadi, Mabroka; Engliez, Souad (Libyan Journal of Science &Technology, 2022)
Interactions between immune and inflammatory cells are mediated primarily through the interaction of proteins, termed interleukins (IL) that are able to promote cell growth, differentiation as well as functional activation. TNF-α, IL-1 and IL-6 are the most important cytokines produced by monocytes. The aim of this study was to investigate the effect of docosahexaenoic acid (DAH), on immune cell proliferation along with cytokine production. This was tested using the THP-1 monocytic cell line, which in turn allowed observing how surface protein cytokine expression was affected by docosahexaenoic acid treatment and whether the effect of incubation would reduce the stimulus-induced production of pro-inflammatory cytokines. The experimental method employed Linked Immunosorbent Assays, while both Cell Titer 96® AQueous One Solution Cell Proliferation Assay and Titer 96 AQueous One Solution were used to determine cell proliferation. THP-1 cells induce growth-promoting activity and, the concentration of DHA toxic effect began at around 100 µM and reached maximum toxicity at around 200 µM. The results demonstrate that DHA inhibited endogenous IL-8 release when compared to a control group where the inhibition was maintained for 3 days. The study revealed the effect of docosahexaenoic acid (DHA), on immune cell proliferation and cytokine production.